Effects of a new cardioselective beta-adrenergic blocker (tolamolol) on exercise tolerance in patients with angina pectoris. Issue 3 (May 1973) - Sood, N. K.; Havard, C. W. H.
Abstract : The effect of oral and intravenous tolamolol on exercise tolerance was assessed in 11 patients with angina pectoris. Patients were selected on the basis of an absence of placebo response and the reliable reproducibility of anginal pain and electrocardiographic changes with exercise on a constant load Schönander-Elema bicycle ergometer. The effect of tolamolol on exercise time and heart rate was compared with that of propranolol. Tolamolol was shown to increase exercise tolerance and the effect was comparable to that of propranolol. Tolamolol did not produce a significant increase in airways resistance nor were any untoward side effects noted.